IMPLEMENTASI TANGGUNG JAWAB DOKTER TERHADAP ASSESMEN BAGI PENGGUNA NARKOTIKA PADA LEMBAGA REHABILITASI NARKOTIKA DI KOTA PEKANBARU - Esprida Hotma Dame; Hasnati Hasnati; Indra Afrita (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2022)
Abstract: Narcotics addicts and victims of narcotics abusers are required to undergo medical and social rehabilitation, in accordance with Article 9 of the Regulation of the Minister of Health No. 2415 Menkes/Per/XII/2011 concerning Medical Rehabilitation for Addicts, Abusers and Narcotics Abuse Victims that the medical rehabilitation process includes assessment, preparation of rehabilitation plans, outpatient or inpatient rehabilitation programs, and post-rehabilitation programs. The results of the study indicate that narcotics abusers who undergo legal processes at the investigation or prosecution stage can undergo medical rehabilitation and social rehabilitation after going through the assessment process. The assessment process is carried out by the Integrated Assessment Team consisting of the Legal Team and the Doctor Team. Through the Integrated Assessment Team, it will be determined whether a suspect or defendant is a narcotics abuser as a narcotics dealer or addict and through the Medical Team the content and severity of narcotics users will be tested. If based on the examination of the Integrated Assessment Team  it is decided that they can undergo medical rehabilitation, the suspect or accused of abusing narcotics will be handed over to a rehabilitation institution. Keywords: Responsibilities, Doctors, Assessment, Narcotics Users  Abstrak: Pecandu narkotika dan korban penyalahguna narkotika wajib menjalani rehabilitasi medis dan sosial, sesuai dengan Pasal 9 Peraturan Menteri kesehatan No. 2415 Menkes/Per/XII/2011 Tentang Rehabilitasi Medis Pecandu, Penyalahguna dan Korban Penyalahgunaan Narkotika bahwa proses rehabilitasi medis meliputi asesmen, penyusunan rencana rehabilitasi, program rehabilitasi rawat jalan atau rawat inap, dan program pasca rehabilitasi. Hasil penelitian menunjukkan bahwa terhadap penyalah guna narkotika yang menjalani proses hukum pada tahap penyidikan atau penuntutan dapat menjalani rehabilitasi medis dan rehabilitasi sosial setelah melalui proses asesmen. Proses asesmen dilaksanakan oleh Tim Asesmen Terpadu yang terdiri dari Tim Hukum dan Tim Dokter. Melalui Tim Asesmen Terpadu akan ditentukan apakah seorang tersangka atau terdakwa penyalah guna narkotika sebagai pengedar atau pecandu narkotika serta melalui Tim Medis akan diuji kandungan serta tingkat keparahan pengguna narkotika. Apabila berdasarkan pemeriksaan Tim Asesmen Terpadu diputuskan dapat menjalani rehabilitasi medis, maka tersangka atau terdakwa penyalah guna narkotika akan diserahkan ke lembaga rehabilitasi. Kata kunci: Tanggung Jawab, Dokter, Assesmen, Pengguna Narkotika